Herpes Zoster In A 3 Month Old Infant - Gangopadhyay D N; Barbhuiya J N; Dey S K (Wolters Kluwer Medknow Publications, 1998)
A case of herpes zoster in a 3 month old female infant is reported. The patient suffered from varicella 1 month prior to onset of herpes zoster, following varicella of mother. Most reported cases of infantile herpes zoster, likely, suffered from varicella during intrauterine life due to maternal varicella during gestational period. Both varicella and herpes zoster during infancy are rare. The disease had an uneventful course with spontaneous healing in our patient.